(untitled) (International Journal of Environmental Sciences, 2024)
The increasing demand for sustainable nutrient management in rice cultivation has intensified interest in organic biofertilizers such as Jeevamrutham. This study evaluated the influence of Jeevamrutham on vegetative growth performance of paddy (Oryza sativa L.) under field conditions using a randomized block design. Key parameters, including plant height, tiller number, leaf area index (LAI) biomass accumulation and soil microbial biomass carbon (MBC) were assessed across different growth stages. Results demonstrated significant improvements in all vegetative traits in plots treated with Jeevamrutham compared to the untreated control, with biomass and MBC showing the highest proportional increases. These findings suggest that Jeevamrutham enhances nutrient mineralization and microbial activity, thereby promoting robust vegetative development. The study highlights Jeevamrutham as a cost-effective, eco-friendly alternative to synthetic fertilizers and underscores its potential for integration into sustainable rice production systems ificant difference in recurrence- free survival between the two groups.